EPICUREAN THEORIES OF KNOWLEDGE FROM HERMARCHUS TO LUCRETIUS AND PHILODEMUS - David Sedley (Lexicon Philosophicum)
The aim of this paper is to trace the development of Epicurean epistemology from the death of Epicurus in 270 BCE to the latter part of the first century BCE. The story gains interest from the fact that these Epicureans were, as would be expected, scrupulously loyal to the doctrines of their founder as they interpreted these, but at the same time found themselves obliged to elaborate and strengthen the inferential methodology he had bequeathed, initially in order to resist the sceptical critiques of the New Academy, and later in order to justify their school’s empiricism in opposition to the rationalistic Stoic theory of inferential validity. The protagonists are Colotes, Polystratus, Timasagoras, Zeno of Sidon, Philodemus and Lucretius, with Cicero an important witness.